Seismic anisotropy across Adria plate, from the Apennines to the Dinarides - Salimbeni, S.; Pondrelli, S.; Molinari, I.; Stipčević, J.; Prevolnik, S.; Dasović, I.; , the AlpArray-CASE working group (Frontiers in Earth Science, 2022)
The Adria microplate has the particular feature to be involved in two subduction systems with slab dipping in opposite directions, one toward west beneath the Apennines and the other to east, beneath the Dinarides. The deep structure of Adria and the shape and characteristics of the slabs have been mainly studied through seismic tomography. However, the uncertainty about the presence and dimensions of tear and windows along the Apennines and the Dinarides slabs is still large. Another instrument used to draw mantle flows and to support the possible presence of slab windows or tears is the detection of seismic anisotropy, in particular core phases shear wave splitting. In this paper, with the purpose to give more light to the structure of Adria slabs and possible mantle circulation beneath this microplate, we benefit from data recorded by seismic stations located along a profile running across the central Adriatic from the Apennines to the edge of the Panonnian basin. The new measurements, together with previous findings, show an evident change of the anisotropic properties when moving along the profile. The distribution of SKS splitting measurements in the Apennines, strongly agree with previous measurements that already described the toroidal flow generated by the slab rollback of the Calabrian arc. Also the N-S and NE-SW directions found beneath the Apulia are in agreement with those attributed previously in the outer northern Apennines, to a proper typical pattern of the mantle beneath Adria, undeformed by the slab retreat. The pattern of the anisotropy in the Dinarides region shows lateral and vertical variations that together with recent tomographic images better defining the slab window, allow us to speculate: the new SKS measurements, interpreted in terms of mantle deformation and flows, agree with the geodynamic model that justify the mantle circulation beneath Adria with the presence of slab windows in both Apennines and Dinarides slabs.